Motivasi, Kepuasan Kerja dan Kinerja Penyuluh Kehutanan di Kabupaten Cianjur Jawa Barat - Firmansyah, Firmansyah; Amanah, Siti; Sadono, Dwi (Jurnal Penyuluhan, 2015)
Performance of forestry extension workers would contribute to the achievement of extension goals. The study aims to find performance of forestry extension workers in relations to their profile, motivation and job satisfaction. The data collection was carried out from March to April 2014 using questionnaires, interviews, observation and literature study. The data obtained were tabulated and analyzed using Pearson correlation. The results showed: (1) most of the forestry extension in Cianjur District has older age categories, has a long working period, higher education level, and frequency of training is low, (2) the level of work motivation were high tended to moderate, work satisfaction were high, and the level of performance including the moderate categories. The results of the Pearson correlation between the motivation and job satisfaction to the performance of forestry extension in Cianjur District shows: (1) there is positive significant correlation between motivation to the performance of forestry extension workers, and (2) There is no significant correlation between the profile of forestry extension and job satisfaction to the performance of forestry extension workers.Key words: forestry extension workers, motivation, job satisfaction, job performance